Quality of Life of Pregnant Women Living with HIV/AIDS - Marysabel Pinto Telis Silveira; Mariângela Freitas Silveira; Cristina Heloisa Müller (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Objective to evaluate the quality of life of HIV positive (HIVþ) pregnant women using the HIV/AIDS Target Quality of Life (HAT-QoL) instrument. Methods cross-sectional study, conducted between May 2014 and November 2015 , with HIVþ pregnant women selected by convenience sampling. Sociodemographic and behavioral data were collected through interviews, and the HAT-QoL questionnaire was applied. Clinical and laboratorial data were collected from medical records. Results twenty-seven pregnant women participated in the study. Their mean age was 27 years (standard deviation - SD: 7.3). The majority (59%) had up to 8 years of education, 52% identified themselves as white, 56% were unemployed, and 59% had a household income higher than the minimum wage. The mean infection time by the virus was 68.4 months (5.7 years). The majority (74%) were contaminated with HIV through sexual intercourse, and 67% declared not having a HIVþrelative. Regarding the use of condoms, 41% reported using them sporadically, and the same number did not have proper knowledge about them. Only 23 patients (85%) reported having been prescribed antiretrovirals. Fourteen (64%) had a CD4 count higher than 500 cells/mm3, and 13 pregnant women (59%) had an undetectable viral load. The scores from the quality of life questionnaire dimensions that were more affected are: infection "disclosure concerns" (mean: 39.8; SD: 27.1), followed by "financial concerns" (mean: 49.1; SD: 36), and "HIV acceptance" (mean: 49.1; SD: 35.8). The dimension with the best score was "medication concerns" (mean: 80.8; SD: 26.5). Conclusion quality of life has been increasingly used as a clinical outcome evaluation parameter. The results of this study contribute to the establishment of interventions based on the needs of HIVþ pregnant women.